2021
DOI: 10.1155/2021/6658943
|View full text |Cite
|
Sign up to set email alerts
|

Research on Fatigue Model of Semi‐Rigid Base Asphalt Pavement before and after Polymer Grouting

Abstract: To improve the service life of a semirigid base asphalt pavement and prolong its service cycle, it is imperative to conduct long-term performance research before and after pavement disease repair. This study proposes a fatigue damage model for pavement and polymer materials and uses the finite element method to establish a three-dimensional numerical model of a semirigid base asphalt pavement structure. Moreover, it compares and analyzes the mechanical response and fatigue damage of this pavement before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The elastic modulus of polyurethane foam samples fluctuated near the initial value with an increase in the soaking time and did not significantly change with soaking time. A few scholars [ 80 , 81 , 82 , 83 ] studied the physical properties of polyurethane foam materials in frozen soil environments and found that the water absorption increased with the increase in soaking time. Figure 5 summarizes the change in the moisture absorption rate of foam materials with soaking time.…”
Section: Effect Of Water Environment On the Polyurethane Foams Materi...mentioning
confidence: 99%
“…The elastic modulus of polyurethane foam samples fluctuated near the initial value with an increase in the soaking time and did not significantly change with soaking time. A few scholars [ 80 , 81 , 82 , 83 ] studied the physical properties of polyurethane foam materials in frozen soil environments and found that the water absorption increased with the increase in soaking time. Figure 5 summarizes the change in the moisture absorption rate of foam materials with soaking time.…”
Section: Effect Of Water Environment On the Polyurethane Foams Materi...mentioning
confidence: 99%
“…Therefore, enhancing the fatigue performance of semi-rigid base layers using advanced technology holds significant practical importance [9,10]. The researchers have investigated the effects of structure design [11,12], aggregate types [13,14], cement properties [15][16][17][18], and aggregate properties [10,[19][20][21] on the fatigue performance of semi-rigid base layers. The idea that adding reinforcement materials in semi-rigid base layers draws inspiration from the concept of adding reinforcements in bridge structures to improve their flexural tensile performance [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…e main disadvantage of cementstabilized macadam in semirigid base asphalt pavements is fatigue cracking under traffic loads over time [13]. Zhang et al [14] compared the mechanical response and fatigue damage of semirigid base asphalt pavement structure before and after repairing reflective cracks with polymer by finite element method. Wang and Ma [15] developed an interlayer contact bonding model to simulate the local bonding state between adjacent layers, and using the established semirigid base asphalt pavement structural model, the effect of temperature on the separation area between the asphalt concrete layer and the base was calculated and analyzed.…”
Section: Introductionmentioning
confidence: 99%